The Procedure for Evaluating the Adsorption Energy Distribution from an Analysis of Thermodesorption Spectra Based on the Statistical Rate Theory - Tomasz Panczyk; Wladyslaw Rudzinski; Tadeusz Borowiecki; Anna Dominko (Adsorption Science & Technology)
We have recently proposed a new method for evaluating the adsorption energy distribution function χ(ε) from the numerical analysis of thermodesorption spectra. This method is based on an application of the Statistical Rate Theory developed by Ward et al . (1982). In this paper, we present some simplifications of this method thereby allowing its ready application. Illustrative calculations for the nitrogen thermodesorption spectra from the surface of molecular sieve carbon fibres (MSCF) are presented.